2015
DOI: 10.1007/s11605-014-2611-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Sacral Neuromodulation Here to Stay? Clinical Outcomes of a New Treatment for Fecal Incontinence

Abstract: SNM is a safe and effective therapy for the treatment of FI. Postoperative patient surveillance is important, as many patients require programming changes, and some will require a lead revision over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…This is in agreement with the significant improvement seen in the CCIS in published literature after commencement of SNM therapy [19,23,[33][34][35].…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with the significant improvement seen in the CCIS in published literature after commencement of SNM therapy [19,23,[33][34][35].…”
Section: Discussionsupporting
confidence: 92%
“…There is a large and growing body of evidence that a defect of the internal or external sphincter is not a contraindication for SNM for FI . Though clinical success has been reported in patients with sphincter defects up to 180 degrees, most would agree that the size of the defect does not matter and should not affect decision making .…”
Section: Fecal Incontinence (Fi)mentioning
confidence: 99%
“…There is a large and growing body of evidence that a defect of the internal or external sphincter is not a contraindication for SNM for FI. 50,[52][53][54][55][56][57][58][59][60][61] Though clinical success has been reported in patients with sphincter defects up to 180 degrees, 13,57,62 most would agree that the size of the defect does not matter and should not affect decision making. 50,54 This is likely because the proposed mechanism of action relies more on sensory nerve fibers and bowel motility than on muscular contraction.…”
Section: Fecal Incontinence (Fi)mentioning
confidence: 99%
“…Tjandra et al studied patients with external sphincter defects up to 120° and demonstrated 100 % continence in 41.5 % and 75 – 99 % improvement over baseline [11]. The neurophysiologic basis underlying this correlation is likely the proposed sensory neuromodulatory effects of SNM rather than a direct effect on the external anal sphincter [9]. …”
Section: Discussionmentioning
confidence: 99%